Mesenteric Cyst in Young Adult Patient: A Case Report - Arzoo, Shabera; Akter, Musammat Shamima; Begum, Nur Jahan; Jannat, Fatematul; Rahman, SM Mahfuzur; Rhaman, SM Tauhidur (Eastern Medical College Journal, 2024)
Mesenteric cysts are rare benign abdominal lesions that possess the risk of malignant transformation in 3% of reported cases. Most cysts are asymptomatic and diagnosed incidentally or during the management of their complications. They may be localized all over the mesentery, from duodenum to rectum, however, they are mostly found in the ileum and right colon mesentery. We present a case report of a 23-year-old female with an abdominal mesenteric cyst. Cyst was excised by laparotomy and resection of some part of small gut also done, without any complications. Eastern Med Coll J. July 2024; 9 (2): 121-124